Effect of Cinnamon Bark Extract (Cinnamomum Burmanii) 50% on Il-6 Levels in Gingiva of Male Wistar Rats (Rattus Norvegicus) Induced by LPS (Lipopolysaccharide) - Wayan Arni Sardi, Ni; Ananda Yudisthira, Made (PT. Publikasiku Academic Solution, 2024)
Periodontitis is a periodontal disease in the form of chronic inflammation of the dental support tissue caused by plaque bacteria. The process of periodontal tissue damage in periodontitis begins with the accumulation of plaque containing bacteria and toxins that are pathogenic. The interaction between plaque bacteria and their products and the body's response to host cells triggers an inflammatory response that can cause ulceration of the gingiva, connective tissue damage, alveolar bone loss, and tooth loss. Periodontitis usually develops from gingivitis that has already occurred, although not all gingivitis progresses to periodontitis. The purpose of this study is to determine the effect of cinnamon bark extract on IL-6 levels. This research method used in vivo laboratory experiments on 32 white rats of the Wistar strain with a research design using a quasi-research model with a posttest only control group design which was randomized into two groups, namely the control group: induced LPS and given Tetracycline gel (Eryzol) topically, the treatment group: induced LPS and given a 50% cinnamon bark extract gel. From the comparative analysis test with the Independent T-Test, it was shown that the significant value of the decrease in IL-6 levels in each group, which was 0.194, was greater than 0.05. This means that there are differences between groups. From the results of the study, it can be said that cinnamon bark extract (Cinnamomum Burmanni) with a concentration of 50% has an effect on reducing IL-6 levels.